Diversidade cultural na diversidade alimentar: comida na Tríplice Fronteira - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Food choices are made as a consequence of social and cultural processes. The culture expressed in food is related to conservation strategies of local agrobiodiversity. The linguistic and cultural diversity present in the students' daily life reflects directly on the food choices of the Triple Frontier (Peru - Brazil - Colombia). The research had as objective to develop didactic material in Spanish Language relating the conservation of agrobiodiversity and food in a contextualized way. To this end, we sought to identify, in the students' daily life, the variety of food consumed in the Triple Frontier; characterize, from the students' perceptions, the agrobiodiversity components used in the preparation of the different local foods; in addition to structuring programmatic contents of the Spanish Language correlating them with the variety of food, local knowledge and agrobiodiversity for contextualized teaching. The research was carried out with students of the 2nd year of Integrated Secondary Education of the Federal Institute of Amazonas - Tabatinga campus, Tabatinga municipality, Amazonas. It was sought to understand, through the interactions of human beings (students' knowledge), the recursive circularity existing between the culture expressed in food and the conservation of local agrobiodiversity. The theoretical approach of the systemic complexity was used as the guiding thread of the research and the Contextualized Case Study model was adopted. It was perceived that the food of the Triple Border is formed from the cultural mixture present, receiving Indian, Brazilian, Colombian and Peruvian influences, independent of geopolitical divisions. Faced with the reality of a system of education that prioritizes disciplinarity and deepens the disarticulation of knowledge in the educational field, it was confirmed the importance of didactic material that enabled the interconnection of knowledge through Environmental Sciences.
Keywords: Alimentação; Conservação da Agrobiodiversidade; Ensino de Espanhol contextualizado; CIÊNCIAS AGRÁRIAS